Validação de sistema automático de monitoramento de comportamento alimentar e efeito da tristeza parasitária sobre o consumo de alimentos em bezerros - Baltazar Ruas de Oliveira Junior (2015)
The objective was to validate a radio frequency system for monitoring individual feeding behavior, water and feed consumption in young cattle housed in group. Thirty five Holstein-Gyr crossbred heifers, fitted with an ear tag containing a unique passive transponder, were distributed in three groups of 12, 12 and 11 animals per period and had free access to 12 electronic feed bins and two electronic water bins (Intergado®, Contagem, Brazil). The system documented the animal, visit duration, individual feed and water intake, bin number, initial and final times of visits, and the difference of feed and water weight at start and end for each visit. Feed bins were monitored by time-lapse video recording over four days and the water bins over six days. For each feed bin, two feeding events were monitored using manual weighings immediately before and after the animals visit and the difference between them was assumed as feed intake (n = 24 observations). For water bins there were made 60 manual weighings. Video and manual weighing data were regressed on the electronic feeding behavior and feed and water intakes data to evaluate systems precision and accuracy. The system showed a high specificity (98.98 and 98.56% for the feed and water bins, respectively) and sensitivity (99.25 and 98.74%, respectively) for identifying animals presence or absence. Duration of feed and water bins visits, and feed and water consumption per visit estimated by the system were highly-correlated and precise (R2 = 0.917, 0.963, 0.973 and 0.986, respectively) when compared to observed video and manual weighing data. In behavioral study the diagnosis of tick-borne occurred by monitoring cell volume (VG) and clinical examination. During the evaluation period 12 animals were affected by tick fever and had the consumption and feeding behaviour evaluated 4 days before and after the diagnosis of illness (d-4 to d4). In d-3 to d4 the daily number of visits to the feeding bins and the total time spent on these visits has reduced. In d-3 and d2 the amount of food ingested at each visit increased. The total daily feed intake was lower in d-1, d0 and d1. The number of water bin visits was lower in d1 and the time spent on these visits was gradually increasing. The water intake per visit was lower in d-3 to d2, and in days d0 and d1 the daily water intake was lower than in other days. It was concluded that Intergado system is a useful tool for monitoring feeding behavior, water and feed intake. All studed variables are changed during the tick-borne disease and some of those changes before the onset of clinical signs of the disease and may be early diagnosis tools, useful in monitoring disease. The alteration of consumption with daily feed intake decrease of 35.5% ,or more, may be an early indicator of tick-borne disease.